From biodiversity to health: Quantifying the impact of diverse ecosystems on human well‐being. Issue 1 (16th December 2022) - Ulrich, Werner; Batáry, Péter; Baudry, Julia; Beaumelle, Léa; Bucher, Roman; Čerevková, Andrea; de la Riva, Enrique G.; Felipe‐Lucia, Maria R.; Gallé, Róbert; Kesse‐Guyot, Emmanuelle; Rembiałkowska, Ewa; Rusch, Adrien; et al.
Abstract: Ample evidence suggests positive effects of species diversity on ecosystem functioning and services in natural and agricultural landscapes. Less obvious and even contested are the effects of such diversity on human well‐being. This state of art partly stems from methodological difficulties to evaluate and quantify these effects and imprecise conceptual frameworks. Here we propose a conceptual framework that links different aspects of diversity, particularly species and genetic richness, to ecosystem functioning, ecosystem services and disservices, and different aspects of well‐being. We review current approaches for the study of diversity–well‐being relationships and identify shortcomings and principle obstacles, mainly stemming from theoretical premises that are too imprecise. We discuss five basic methodological approaches to link diversity to well‐being: matrix models, indirect inference, Price partitioning, structural equation modelling, and environmental inference. We call for a stricter terminology with respect to the different aspects of functioning, multifunctionality and well‐being and highlight the need to evaluate each step in the different pathways from diversity to well‐being. A full understanding of ecological constraints on human well‐being requires consideration of trade‐offs in diversity effects, of contrasting perceptions of well‐being, and of ecosystem disservices. We also call for appropriate long‐term socio‐ecological research platforms to gather relevant data about ecosystem functioning and well‐being across space and time. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Zusammenfassung: Zahlreiche Befunde deuten auf eine positive Auswirkung der Artenvielfalt auf das Funktionieren und die Leistungen von Ökosystemen in Natur‐ und Agrarlandschaften hin. Weniger offensichtlich und sogar umstritten sind die Auswirkungen einer solchen Vielfalt auf das menschliche Wohlergehen. Diese Wissenslücke ist teilweise auf methodologische Schwierigkeiten bei der Bewertung und Quantifizierung dieser Effekte und auf ungenaue konzeptionelle Rahmenbedingungen zurückzuführen. Wir schlagen hier einen konzeptionellen Rahmen vor, der verschiedene Aspekte der Vielfalt, insbesondere des Arten‐ und genetischen Reichtums, mit Ökosystemfunktionen, Ökosystemleistungen und ‐dysfunktionen und verschiedenen Aspekten des Wohlergehens verbindet. Wir beleuchten aktuelle Ansätze zur Untersuchung von Beziehungen zwischen Vielfalt und Wohlergehen und identifizieren Mängel und prinzipielle Hindernisse, die hauptsächlich auf zu ungenauen theoretischen Prämissen beruhen. Wir diskutieren fünf grundlegende methodologische Ansätze, um Diversität mit Wohlergehen zu verknüpfen: Matrixmodelle, indirekte Inferenz, Price‐Partitionierung, Pfadanalysen und Umweltinferenz. Wir plädieren für eine strengere Terminologie in Bezug auf die verschiedenen Aspekte des Funktionierens, der Multifunktionalität und des Wohlergehens und betonen die Notwendigkeit, jeden Schritt auf den verschiedenen Pfaden von der ökologischen Vielfalt zum Wohlergehen zu bewerten. Ein vollständiges Verständnis der ökologischen Einschränkungen des menschlichen Wohlergehens erfordert die Berücksichtigung der Balance bei Diversitätseffekten, von gegensätzlichen Wahrnehmungen des Wohlergehens und von Ökosystemdysfunktionen. Wir fordern auch geeignete langfristige sozio‐ökologische Forschungsplattformen, um relevante Daten über das Funktionieren von Ökosystemen in Bezug auf das menschliche Wohlergehen in Raum und Zeit zu sammeln. Abstraktné: Množstvo dôkazov poukazuje na pozitívny vplyv diverzity na fungovanie ekosystémov a ich úlohy v prírodnej a poľnohospodárskej krajine. Menej zrejmé a dokonca otázne sú ale účinky takejto diverzity na blahobyt ľudí. Tento stav čiastočne vyplýva z metodických ťažkostí pri posudzovaní týchto účinkov a nepresných koncepčných rámcov. V tejto práci navrhujeme koncepčný rámec, ktorý spája rôzne aspekty diverzity s fungovaním ekosystémov, jej úlohou, negatívnymi účinkami a blahobytom. Preskúmame súčasné prístupy k štúdiu vzťahov medzi diverzitou a blahobytom a identifikujeme nedostatky a zásadné prekážky, ktoré vyplývajú najmä z príliš nepresných teoretických východísk. V práci rozoberáme päť základných metodologických prístupov k spojeniu diverzity a blahobytu a to: maticové modely, nepriamu inferenciu, rozdelenie podľa ceny, modelovanie štrukturálnych rovníc a inferenciu podľa prostredia. Žiadame o presnejšiu terminológiu s ohľadom na rôzne aspekty fungovania, multifunkčnosti a blahobytu a zdôrazňujeme potrebu vyhodnotiť každý krok na jednotlivých cestách od diverzity k ľudskému blahobytu. Úplné pochopenie ekologických obmedzení ľudského blahobytu si vyžaduje, aby sa zohľadňovali kompromisy v účinkoch diverzity, kontrastného vnímania blahobytu a negatívnych účinkov ekosystémových služieb. Tiež žiadame o vytvorenie vhodných dlhodobých sociálno‐ekologických výskumných platforiem, ktoré by zhromažďovali relevantné údaje o fungovaní ekosystémov a o ľudskom blahobyte v priestore a čase. Abstrakt: Wiele dowodów wskazuje na pozytywny wpływ różnorodności na funkcjonowanie ekosystemów i ich usługi w krajobrazach naturalnych i rolniczych. Mniej oczywiste, a nawet kwestionowane są skutki takiej różnorodności dla dobrostanu człowieka. Ten stan rzeczy wynika częściowo z trudności metodologicznych w ocenie tych skutków oraz nieprecyzyjnych ram koncepcyjnych. W tym miejscu proponujemy ramy koncepcyjne, które łączą różne aspekty różnorodności z funkcjonowaniem ekosystemu, usługami i nie‐zasługami ekosystemu oraz dobrostanem. Dokonujemy przeglądu obecnych podejść do badania relacji różnorodność ‐ dobrostan i identyfikujemy braki i zasadnicze przeszkody, wynikające głównie ze zbyt nieprecyzyjnych założeń teoretycznych. Omawiamy pięć podstawowych podejść metodologicznych do powiązania różnorodności z dobrostanem: modele macierzowe, wnioskowanie pośrednie, podział Price'a, modelowanie równań strukturalnych i wnioskowanie środowiskowe. Wzywamy do wprowadzenia bardziej rygorystycznej terminologii w odniesieniu do różnych aspektów funkcjonowania, wielofunkcyjności i dobrostanu oraz podkreślamy potrzebę oceny każdego kroku na różnych ścieżkach od różnorodności do dobrostanu. Pełne zrozumienie ekologicznych ograniczeń dobrostanu człowieka wymaga uwzględnienia kompromisów w zakresie skutków różnorodności, kontrastowego postrzegania dobrostanu oraz usług ekosystemów. Wzywamy również do stworzenia odpowiednich długoterminowych platform badawczych o charakterze społeczno‐ekologicznym w celu zebrania odpowiednich danych na temat funkcjonowania ekosystemów i dobrostanu w przestrzeni i czasie.